2010
DOI: 10.1167/10.12.2
|View full text |Cite
|
Sign up to set email alerts
|

The development of the ability of infants to utilize static cues to create and access representations of object shape

Abstract: A “transfer-across-depth-cues” method was used to explore the development of the ability to generate and use spatial representations of an object as specified by static pictorial depth cues. Infants were habituated to an object with depth specified by one cue and then presented with the same shape with depth specified by a different cue. Only if an abstract representation of that object had been formed could transfer across cues occur. Shading and line junctions uniquely determined the 3D shapes in these displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Imura et al (2008) showed that 7-to 8-month-old infants perceived pictorial depth cues defined by shading and line junction as well. Tsuruhara et al (2010) support the hypothesis that the ability to form three-dimensional spatial representations of an object from pictorial depth cues emerges at about 6 to 7 months of age. These findings imply that view perception develops during 6 to 8 months of age.…”
Section: Introductionsupporting
confidence: 78%
“…Imura et al (2008) showed that 7-to 8-month-old infants perceived pictorial depth cues defined by shading and line junction as well. Tsuruhara et al (2010) support the hypothesis that the ability to form three-dimensional spatial representations of an object from pictorial depth cues emerges at about 6 to 7 months of age. These findings imply that view perception develops during 6 to 8 months of age.…”
Section: Introductionsupporting
confidence: 78%
“…Bhatt & Waters, 1998; Shuwairi, Albert & Johnson, 2007), while other studies could not support this finding (e.g. Tsuruhara et al 2009, 2010). The latter studies might underestimate younger infants’ perceptual abilities, with more demanding tasks such as extracting 3-D form information.…”
Section: Discussionmentioning
confidence: 61%
“…On the other hand, studies using the habituation/dishabituation method (e.g. Tsuruhara et al 2009, 2010) have found evidence of sensitivity to pictorial depth cues around 6-months, but not in younger infants.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…They documented that 7-month-old infants preferred to reach for the object that was perceived from shadings or cast shadows as being nearer. Additionally, a previous study used looking behavior to show that 6-to 7-month-old infants can represent 3-D shapes from pictorial depth cues (i.e., shadings; Tsuruhara et al, 2010;Tsuruhara, Sawada, Kanazawa, Yamaguchi, & Yonas, 2009). Tsuruhara and her colleagues used a transfer-across-cue paradigm to test infants' ability to represent 3-D shapes.…”
Section: Discussionmentioning
confidence: 99%